Morphological aspects of seeds and seedlings of Syagrus oleracea (MART.) BECC – Arecaceae - Batista, Gisele Sales; Costa, Raquel Silva; Gimenes, Renata; Pivetta, Kathia Fernandes Lopes; Môro, Fabíola Vitti (Comunicata Scientiae, 2011)
The Syagrus oleracea (Mart.) Becc palm, although widely used in Brazilian landscaping, is poorly studied, especially, regarding seedlings production. Studies on ‘seed’ (botanically, a pyrene) and seedling morphology of this palm have not been found, although it has a great market demand. Thus, this study aimed to describe the seeds and seedlings morphology of S. oleracea. The morphology of seeds, the embryos and the phases representing the germination process were sketched with the aid of clear camera attached to a stereomicroscope. The fruit is a drupe and the seeds are albuminous with ruminated endosperm of hard consistency and occupying almost the entire interior of the seeds. The embryo is lateral, peripheral, poorly differentiated and rectum. Through the opening of a circular operculum in wraps seeds, emerges cotyledon petiole that grows and expands at its end, resulting in the primary root and shoot. The first juvenile complete leaf is simple and lanceolated, with parallel venation, composed of large veins, arranged longitudinally. The germination of the S. oleracea seeds is of remote tubular type.